Stage-directed therapy of pleural empyema - Reichert, Martin; Weigand, Markus A. (Langenbeck's archives of surgery, 2017)
PurposeIntensivists and surgeons are often confronted with critically ill patients suffering from pleural empyema. Due to it’ s multifactorial pathogenesis and etiology, medicals should be sensitized to recognize the different stages of the disease. Besides a whole bundle of different established classification systems, the progress of pleural effusions can be subdivided into the early exudative, the intermediate fibropurulent and the late organized phase according to the classification of the American Thoracic Society.ResultsRapid diagnosis of pleura empyema is essential for patients’ survival. Due to the importance of stage-adapted therapeutic decisions, different classification systems were established. Depending on the stage of pleural empyema, both antimicrobial and interventional approaches are indicated. For organized empyema, minimally invasive and open thoracic surgery are gold standard. Surgery is based on the three therapeutic columns: removal of pleural fluid, debridement and decortication. In general, therapy must be intended stage-directed following multidisciplinary concepts including surgeons, intensivists, anesthesiologists, physiotherapists and antibiotic stewards. Despite an established therapeutic algorithm is presented in this review, there is still a lack of randomized, prospective studies to evaluate potential benefits of minimally invasive (versus open) surgery for end-stage empyema or of catheter-directed intrathoracic fibrinolysis (versus minimally invasive surgery) for intermediate-stage pleural empyema. Any delay in adequate therapy results in an increased morbidity and mortality.ConclusionThe aim of this article is to review current treatment standards for different phases of adult thoracic empyema from an interdisciplinary point of view.
First Online: 04 November 2016
Gesehen am 03.05.2018